THE ANTHROPOLOGICAL DIMENSION OF COMMUNICATION IN THE MODERN EDUCATIONAL PROCESS - Mershchii, Tetiana (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2025)
Modern education is transforming due to ICT technologies, which reshape learning culture, student identity, and relationships. The war in Ukraine adds unique challenges, impacting the education system and emotional well-being. The aim of the study is to explore the anthropological dimension of communication in contemporary education, particularly in the context of online learning amidst the war in Ukraine. Research methodology incorporates cultural-historical, sociocultural, and synergetic approaches. The cultural-historical approach explores communication in education through cultural traditions and historical shifts, including the war in Ukraine, revealing its effects on teacher-student interactions and social skills in online learning. The sociocultural approach examines social interactions and contexts, focusing on how technology reshapes cultural identity and how the war impacts emotional connections in education. The synergetic approach analyzes education as a dynamic system, highlighting how wartime online learning influences communication, educational effectiveness, and skill development. Research results. The advent of the Internet and digital technologies has radically transformed communication practices, creating a "networked society" (M. Castells). In education, the shift to digital technologies has driven the rise of online courses and virtual classrooms, transforming interaction dynamics. Castells highlights that networked interaction enables global collaboration, expanding learning opportunities while involving emotional components. Tools like chats, video conferencing, and online forums reshape engagement, facilitating real-time lessons and access to resources from anywhere. In Ukraine, the war has significantly altered education, emphasizing distance learning and introducing challenges like declining attendance, educator shortages, and the need for adapted assessments, profoundly impacting the educational experience. Discussion. New forms of student-teacher interaction reflect shifting cultural norms, necessitating analysis through philosophy of education. Conclusions. Research shows that limited face-to-face communication hinders younger students’ social skill development, especially in war contexts where psychological stress challenges pedagogy. Remote learning decreases emotional connections, fostering isolation and impacting motivation, further exacerbated by anxiety and uncertainty. In Ukraine, educational losses stem from stress and disrupted learning processes, highlighting the need for innovative approaches to communication in education. Support programs are emerging, but their effectiveness requires philosophical evaluation to improve educational culture